Bridal Parade Music As A Cultural Expression of The Kikim in Lahat Regency - Effendi, Widia; Utomo, Udi; widodo, Widodo (Universitas Negeri Semarang, 2021)
One of the arts that is very full of Islamic nuance with the Kikim Tribe is the art of “Arakan” or